Pengaruh Prinsip Good Corporate Governance (GCG), Manajemen Risiko, dan Budaya Organisasi terhadap Kinerja Keuangan: Studi Empiris pada KSP di Kabupaten Magelang - Lestari, Eka Reni; Purwantini, Anissa Hakim (Jurnal Nuansa Karya Akuntansi, 2023)
This study aims to test and analyze empirically the influence of the principles of good corporate governance (GCG), risk management and organizational culture on financial performance. The population in this study were KSP employees in Magelang Regency. The sample used in this study was 75 samples using a purposive sampling technique. The analytical tool used in this study is multiple linear regression. Based on the results of the t test, it is known that the variables of transparency, accountability and risk management have a positive effect on financial performance. Meanwhile, the variables of responsibility, independence, fairness and organizational culture have no effect on financial performance.